Emerging microRNA biomarkers for colorectal cancer diagnosis and prognosis. Issue 1 (23rd January 2019) - Chen, Bing; Xia, Zijing; Deng, Ya-Nan; Yang, Yanfang; Zhang, Peng; Zhu, Hongxia; Xu, Ningzhi; Liang, Shufang
Abstract : Abstract : MicroRNAs (miRNAs) are one abundant class of small, endogenous non-coding RNAs, which regulate various biological processes by inhibiting expression of target genes. miRNAs have important functional roles in carcinogenesis and development of colorectal cancer (CRC), and emerging evidence has indicated the feasibility of miRNAs as robust cancer biomarkers. This review summarizes the progress in miRNA-related research, including study of its oncogene or tumour-suppressor roles and the advantages of miRNA biomarkers for CRC diagnosis, treatment and recurrence prediction. Along with analytical technique improvements in miRNA research, use of the emerging extracellular miRNAs is feasible for CRC diagnosis and prognosis.